Impact of Website Design and Product Image Quality on Efficient Online Shopping Experiences - Sharma, Rashmi; Datt, Sachin; Sachdeva, Kanika (Indian Journal of Marketing, 2025)
Purpose : The present study aimed to examine the role of website design, product pictures, and their qualities in facilitating the online shopping experience for consumers. The world economy has moved its paradigm from a manufacturing to a service-driven economy, where international market dynamics, changing consumer expectations, and technological advancements have led to cut-throat competition and complexities, especially in the online shopping domain. The current study, therefore, aimed to evaluate the effect of website design quality and high-quality product images on consumers’ trust, e-satisfaction, and online shoppers’ pleasure. Design/Methodology/Approach : A structured questionnaire was administered using quota sampling to collect primary data from 220 customers from Delhi and Gurugram. Customers frequently use e-commerce websites (Flipkart, Amazon, Meesho, and Myntra) to shop online. In India, a pilot study was first performed to ensure the questionnaire’s reliability. Findings : We found that product image quality and website design quality significantly improved e-satisfaction, which in turn affected user shopping loyalty. The findings suggested that the quality of product images alone had a significant impact on e-satisfaction, highlighting the importance of visual appeal in stimulating positive consumer responses. Practical Implications : Using the study’s findings and the impact of different variables on customer trust and e-satisfaction, marketers were able to develop strategies that emphasized multicultural marketplaces. Originality/Value : Unlike prior research, the current study established the foundation for understanding changing customer preferences regarding visual appeals and their dimensions in affecting customer loyalty toward websites.